How Much Water in Basaltic Melts Parental to Porphyry Copper Deposits? - Chiaradia, Massimo (Frontiers in Earth Science, 2020)
Porphyry copper deposits are formed by aqueous fluids exsolved by differentiated, mantle-derived magmas variably mixed with crustal melts. Water is essential to form porphyry Cu mineralization and explains why these deposits are found only at convergent margin settings, where subduction has enriched the mantle source of magmas with slab-derived H2O. Intuitively, the more water occurs in the parental magmas of porphyry deposits the more fertile the latter should be. Indeed, several studies have proposed that anomalously high H2O contents in the source basalt, resulting for instance from subduction of large-scale serpentinized fracture zones of the oceanic slab, could increase the fertility of magmas. However, no studies have ever quantified the effects of variable H2O contents on the fertility of parental basalts to form porphyry deposits. Here, using petrological modelling with a Monte Carlo approach, I show that the optimum amount of slab-derived H2O in fertile parental basalts is ~2-6 wt.%, which coincides with the measured range of H2O content in arc basalts. Lower and higher amounts of H2O in the parental basalt lead to less porphyry-fertile magmas. The lower fertility of H2O-poor parent basalt (i.e., <2 wt.%) predicted by the model is understandable as the result of an overall lower amount of fluid that can be exsolved by the magmatic system once it reaches H2O saturation. In contrast, the decrease in fertility of H2O-rich parental basalts (>6 wt.%) predicted by the model is counterintuitive. The reason of decreased fertility of parental basalts with >6 wt.% H2O is that such H2O-rich magmas undergo fluid saturation losing their fluid and metal cargo at deep crustal levels. Additionally, water saturation-induced crystallization of amphibole at these deep levels prevents such H2O-rich magmas from ascending to shallower crustal levels, from where only they can form porphyry deposits. The conclusion that arc basalts with normal H2O contents (~2-6 wt.%) are the most porphyry-fertile adds evidence to the hypothesis that intermediate-felsic magmas associated with porphyry Cu deposits are parented by arc basalts formed through normal subduction-related processes, and that intracrustal and tectonic processes play the most relevant role in the modulation of Cu endowments of these deposits.